Socioecological model-based design and implementation principles of lower limb preservation programs as partners for limb-loss rehabilitation programs— A mini-review - Khetarpaul, Vipul; Kirby, John P.; Geraghty, Patrick; Felder, John; Grover, Prateek (Frontiers in Rehabilitation Sciences, 2022)
People with lower limb loss, especially of dysvascular etiology, are at substantial risk for both ipsilateral and contralateral reamputation. Additionally, while not as well documented for reamputation, there is recognition that amputation incidence is influenced by not only sociodemographic factors such as sex, race, socioeconomic status, but also by system factors such as service access. A systems strategy to address this disparity within the field of limb-loss rehabilitation is for Limb-loss Rehabilitation Programs (LRP) to partner with medical specialists, mental health professionals, and Limb Preservation Programs (LPP) to provide comprehensive limb care. While LPPs exist around the nation, design principles for such programs and their partnership role with LRPs are not well established. Using a socioecological model to incorporate hierarchical stakeholder perspectives inherent in the multidisciplinary field of limb care, this review synthesizes the latest evidence to focus on LPP design and implementation principles that can help policymakers, healthcare organizations and limb-loss rehabilitation and limb-preservation professionals to develop, implement, and sustain robust LPP programs in partnership with LRPs.